2021
DOI: 10.3389/fevo.2021.746254
|View full text |Cite
|
Sign up to set email alerts
|

Cortex Thickness Is Key for the Colors of Iridescent Starling Feather Barbules With a Single, Organized Melanosome Layer

Abstract: The iridescent plumage of many birds is structurally colored due to an orderly arrangement of melanosomes in their feather barbules. Here, we investigated the blue- to purple-colored feathers of the European starling (Sturnus vulgaris) and the blue and green feathers of the Cape starling (Lamprotornis nitens). In both cases, the barbules contain essentially a single layer of melanosomes, but in S. vulgaris they are solid and rod-shaped, and in L. nitens they are hollow and rod- as well as platelet-shaped. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Some studies have suggested that the keratin cortex surrounding multilayered melanosomes affects the colours of bird feathers [16,37,38,45]. Of these, most have considered keratin cortices of different thicknesses with theoretical models [36][37][38]46], statistical analyses [33,45] and by observing barbule samples where the keratin cortex had been accidentally removed [36,37]. Specifically, based on a quantitative optical modelling of multi-layered melanosomes in mallard barbules-a very similar system to the pheasant feathers examined in this study-Stavenga et al [38] have convincingly explained the effect of changing barbule cortex thickness on the iridescent colours produced by multi-layered melanosomes on the hue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have suggested that the keratin cortex surrounding multilayered melanosomes affects the colours of bird feathers [16,37,38,45]. Of these, most have considered keratin cortices of different thicknesses with theoretical models [36][37][38]46], statistical analyses [33,45] and by observing barbule samples where the keratin cortex had been accidentally removed [36,37]. Specifically, based on a quantitative optical modelling of multi-layered melanosomes in mallard barbules-a very similar system to the pheasant feathers examined in this study-Stavenga et al [38] have convincingly explained the effect of changing barbule cortex thickness on the iridescent colours produced by multi-layered melanosomes on the hue.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous research has studied the effects of changing the thickness of the keratin cortex on the glossiness of black barbules [44], iridescence from poorly ordered melanosomes [36] and iridescence from single-layered melanosomes [37]. Some studies have suggested that the keratin cortex surrounding multi-layered melanosomes affects the colours of bird feathers [16,37,38,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has focused on the fundamentals underlying those natural photonic systems, as well as on their implications in nature and how to utilize them as inspiration in biomimicry. There is a vast amount of work on understanding the photonic properties of nano-scale structures found in a variety of animals, spanning from insects [ 1 , 2 , 3 , 4 ] to shellfish [ 5 , 6 ], birds [ 7 , 8 , 9 ] and beyond [ 10 , 11 ]. Animals employ photonic nanostructures for varied behaviours, such as displaying colour in mating or as aposematism, in pattern production and vision [ 12 ].…”
Section: Introductionmentioning
confidence: 99%